2020
DOI: 10.1016/j.omtn.2020.10.026
|View full text |Cite
|
Sign up to set email alerts
|

circEYA1 Functions as a Sponge of miR-582-3p to Suppress Cervical Adenocarcinoma Tumorigenesis via Upregulating CXCL14

Abstract: Circular RNAs (circRNAs) function as efficient microRNA (miRNA) sponges that regulate gene expression in the pathogenesis of many human malignancies. However, their roles in cervical adenocarcinoma remain largely unknown. In this study, we aimed to seek novel circRNAs that regulate cervical adenocarcinoma carcinogenesis and to explore their regulatory mechanisms as well as clinical significance. We identified that 24 circRNAs were differentially expressed in cervical adenocarcinoma tissues by RNA sequencing. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…In our HeLa cell experiment, the main fragment was 61 nt, which indicates a unique fragment given that we had a maximum read length of 75 nt. Even though the methods used in Tong et al (25) and Xu et al (26, 27) were restricted to a maximum read length of 50 nt, we found traces of this fragment in the pile of fragments with unverifiable length of ≥ 50 nt. It must be emphasized, however, that we tried to validate the 5’ ETS rRF in yet another dataset, Snoek et al (62) (SRA accession: PRJNA413777), but here we failed to detect anything in the 5’ EST region.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In our HeLa cell experiment, the main fragment was 61 nt, which indicates a unique fragment given that we had a maximum read length of 75 nt. Even though the methods used in Tong et al (25) and Xu et al (26, 27) were restricted to a maximum read length of 50 nt, we found traces of this fragment in the pile of fragments with unverifiable length of ≥ 50 nt. It must be emphasized, however, that we tried to validate the 5’ ETS rRF in yet another dataset, Snoek et al (62) (SRA accession: PRJNA413777), but here we failed to detect anything in the 5’ EST region.…”
Section: Discussioncontrasting
confidence: 56%
“…Despite only having read lengths of 50 nt to our disposal (see Results 7.1), where 5’ ETS rRF of Peak 1 was 61 nt, we found clear traces of this rRF (Figure 8J). Furthermore, to explore the clinical relevance of this finding we downloaded the Xu et al dataset (26, 27). Here sRNA was extract from confirmed cervical tumors and samples from normal cervix.…”
Section: Results and Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…To independently evaluate and define the LINC01016 gene structure, RNA-Seq datasets (20-22) were obtained, and splice events were determined based on de novo predictions for LINC01016 in the testis (Fig. 4A) and cervix (Fig.…”
Section: Resultsmentioning
confidence: 99%